Optimasi Pertumbuhan Anggrek Dendrobium sp. Fase Seedling dengan Pemberian Variasi Dosis Pupuk - Erma Lintang Sari; Maria Ulfah; Lussana Rossita Dewi (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2024)
This research aimed to find out what variations in fertilizer doses are optimal to stimulate the growth of orchids in the seedling phase. The method used was a Completely Randomized Design (CRD) method with one factor, namely the concentration of Grow More leaf fertilizer with 3 treatments and 5 replications. The treatments given were fertilizer concentrations of 0.2 g/200 mL, 0.4 g/200 mL, and 0.6 g/200 mL. The data obtained were analyzed using Anova analysis with an accuracy of 0.05. The research results showed that variations in fertilizer doses had no significant effect on the research parameters of plant height, new shoot height and new root length. Meanwhile, it has a real effect on the parameters of the number of new roots. In conclusion, a fertilizer concentration of 0.6 g/ 200 mL is the optimal concentration for the growth of the number of new roots of Dendrobium orchids in the seedling phase. Keywords: Orchid, Dendrobium, Fertilizer Dosage, Seedling Phase